Advanced Optimal for Power-Electronic Systems for the Grid Integration of Energy Sources - Salam Waley Shneen (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Renewable and clean energies like a photovoltaic (PV) energy and wind energy (WE), they can contribute in decreasing the electric energy cost. Energy storage is necessary in PV and WE hybrid system with the variable nature. A hybrid system (PV, WE and diesel), it uses the aim of minimizing the total cost and ensuring the energy available. In this paper, the modeling and cost analysis of a hybrid system (PV, WE and diesel) considering three types systems: First, diesel with a hybrid system. Second, diesel and battery with a hybrid system. Third, grid, battery and hybrid system. In comparison to all types, for cost analysis, a mathematical model have introduced for each type. There are two parts of this work. First by Homer software, it has been used to find the system feasibility and conduct the economic analysis. Second by Matlab simulation, this paper includes status of grid integration in one day through twenty four. The power generation by wind turbine, the change of wind speed which effect on values of power generation. The power generation by solar cell, the change of temperature and radiation which effect in values of power generation.